Information Seeking Behaviour of Undergraduates about Higher Educational Opportunities in Sri Lanka: Online or Offline? (Proceedings of the International Conference on Future of Education, 2020)
International Degree Programmes emerged as a domestic option affiliated to privatehigher educational institutes (PHEIs). As it is highly competitive, PHEIs implement their BDprogrammes differently to attract prospective student where social media platforms use todisseminate more informed information. However, this study attempts to discuss howundergraduates seek information at an early stage of their decision-making process when selecting aBD. The questionnaire with 59 predefined variables administered by 420 first-year undergraduatesfrom randomly selected 7 PHEIs. Educating stakeholders for the digital world is significant since thepenetration of social media still plays a secondary role in seeking information.
Keywords: Bachelor’s Degree; Gender Differences; information sources; Prospective Students; Social Media